Relationship between Respiratory Load Perception and Perception of Nonrespiratory Sensory Modalities in Subjects with Life-Threatening Asthma - Kathleen L. Davenport; Chien Hui Huang; Matthew P. Davenport; Paul W. Davenport (Pulmonary Medicine)
Subjects with life-threatening asthma (LTA) have reported decreased sensitivity to inspiratory resistive (R) loads. It is unknown if decreased sensitivity is specific for inspiratory R loads, other types of respiratory loads, or a general deficit affecting sensory modalities. This study hypothesized that impairment is specific to respiratory stimuli. This study tested perceptual sensitivity of LTA, asthmatic (A), and nonasthmatic (NA) subjects to 4 sensory modalities: respiratory, somatosensory, auditory, visual. Perceptual sensitivity was measured with magnitude estimation (ME): respiratory loads ME, determined using inspiratory R and pressure threshold (PT) loads; somatosensory ME, determined using weight ranges of 2–20 kg; auditory ME, determined using graded magnitudes of 1 kHz tones delivered for 3 seconds bilaterally; visual ME, determined using gray-to-white disk intensity gradations on black background. ME for inspiratory R loads lessened for LTA over A and NA subjects. There was no significant difference between the 3 groups in ME for PT inspiratory loads, weight, sound, and visual trials. These results demonstrate that LTA subjects are poor perceivers of inspiratory R loads. This deficit in respiratory perception is specific to inspiratory R loads and is not due to perceptual deficits in other types of inspiratory loads, somatosensory, auditory, or visual sensory modalities.